Development of novel sonoprocessing based bi- and triphasic systems for the extraction of biomolecules from microalgae - Chia, Shir Reen (2021)
Microalgae have great potentiality to act as reservoirs of viable bioactive compounds due to the attractive composition of high value-added compounds. Besides, lots of advantages have been reported using microalgae compared to plant-based biomolecules as it does not create food competition and has rapid growth rate. The resistant microalgae cell wall has to be overcome through effective yet simple and rapid techniques in separating desired compounds from the biomass for further applications. The conventional processes for processing biomass in the current industries is inefficient and not feasible to be applied on microalgae, at which a cost- and time-saving technique is in desperate need for the efficient production of biomolecules.